2017
DOI: 10.1504/mejm.2017.087522
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the use of knowledge management tools within the Saudi Arabian public sector organisations

Abstract: Recent technological developments have made a significant and positive impact on the ability and desire to manage knowledge. Therefore, the aim of this paper is to explore the usage of key knowledge management (KM) techniques and technologies for dealing with change initiatives in the Kingdom of Saudi Arabia (KSA) public sector organisations. A web-based, online questionnaire survey method was employed to collect data. The survey revealed that conventional, simple and cost-effective KM techniques and technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, technologies and social systems are equally important in KM. Renukappa et al, (2017) noted that tools are usually required to facilitate KM. The authors argued that, just as it can prove difficult to arrive at a single definition of KM, firm definitions of KM tools can also prove elusive owing to the lack of consensus regarding what constitutes a KM tool.…”
Section: Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, technologies and social systems are equally important in KM. Renukappa et al, (2017) noted that tools are usually required to facilitate KM. The authors argued that, just as it can prove difficult to arrive at a single definition of KM, firm definitions of KM tools can also prove elusive owing to the lack of consensus regarding what constitutes a KM tool.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…With these strategies, knowledge is managed with techniques focusing on people and their interaction rather than on ICT (Črešnar et al, 2019). Renukappa et al, (2017) noted that not all tools are IT based but much emphasis is placed on the electronic tools due to their dynamic capabilities, quick evolution, and organisational impacts. Egbu, et al, (2005) noted that non-IT tools are termed as KM techniques and the IT tools termed as KM technologies.…”
Section: Knowledge Managementmentioning
confidence: 99%
“…Lin and Hwang (2014) indicated that knowledge resources reside in employees' minds and organizations have to utilize this valuable resource for their competitive advantage. At the heart of an organization's strategy process, it has been observed that it is a force, which has been termed as the 'knowledge force,' which is powered by the knowledge workers (Renukappa et al, 2017).…”
Section: Knowledge Managementmentioning
confidence: 99%